Pizza and Taco : who's the best? - Shaskan, Stephen (2020)
Best friends Pizza and Taco agree on nearly everything until Pizza declares himself the best of all, leading to debating, voting, competing, and finally defining what being the best really means.
"A Stepping Stone Book."
Keywords: Graphic novels; Best friends -- Fiction; Friendship -- Fiction; Pizza -- Fiction; Tacos -- Fiction; Contests -- Fiction; Graphic novels